Bone marrow mesenchymal stem cells-derived exosomes for penetrating and targeted chemotherapy of pancreatic cancer - Yu Zhou; Wenxi Zhou; Xinli Chen; Qingbing Wang; Chao Li; Qinjun Chen; Yu Zhang; Yifei Lu; Xiaoyi Ding; Chen Jiang (Elsevier, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most intractable malignancy, with an only 6% 5-year relative survival rate. The dismal therapeutic effect is attributed to the chemotherapy resistance and unique pathophysiology with abundant inflammatory cytokines and abnormal hyperplasia of extracellular matrix (ECM). Based on the theory that bone marrow mesenchymal stem cells (BM-MSCs) can influence the tumorous microenvironment and malignant growth of PDAC, we employed exosomes (Exos) derived from BM-MSCs as PDAC-homing vehicles to surpass the restrictions of pathological ECM and increase the accumulation of therapeutics in tumor site. To overcome chemoresistance of PDAC, paclitaxel (PTX) and gemcitabine monophosphate (GEMP)-an intermediate product of gemcitabine metabolism-were loaded in/on the purified Exos. In this work, the Exo delivery platform showed superiorities in homing and penetrating abilities, which were performed on tumor spheroids and PDAC orthotopic models. Meanwhile, the favorable anti-tumor efficacy in vivo and in vitro, plus relatively mild systemic toxicity, was found. Loading GEMP and PTX, benefitting from the naturally PDAC selectivity, the Exo platform we constructed performs combined functions on excellent penetrating, anti-matrix and overcoming chemoresistance (Scheme 1). Worth expectantly, the Exo platform may provide a prospective approach for targeted therapies of PDAC.